MET235THR POLYMORPHISM IN THE AGT GENE IN THE DEVELOPMENT OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS WHO HAVE HAD COVID-19 IN THE UZBEK POPULATION (Proceedings of International Educators Conference, 2024)
During the COVID-19 pandemic, many large studies have confirmed a direct relationship between the severity of the infectious disease and a history of diabetes mellitus. According to the observations of Chinese scientists, the majority of deaths were observed among patients with comorbid pathologies, including hypertension (53.8%), diabetes (42.3%), heart disease (19.2%) and strokes (15.4%). In Italy, the sickest patients requiring treatment in the intensive care unit often had hypertension (49%), other cardiovascular diseases (21%) and diabetes (17%). The severe course of Covid-19 in patients with diabetes mellitus against the background of cardiovascular pathology is associated with the development of endothelial dysfunction, which prompted us to begin our own research in this area.